A cultural revolution. (2nd January 2020) - Marsh, Sian; Mason, Gill
Abstract : A focus on the unique child is key to understanding how cultural capital relates to best practice. Here Sian Marsh of Best Practice Network highlights the approach of Kids Planet Day Nurseries.